Role of PSMA PET-guided metastases-directed therapy in oligometastatic recurrent prostate cancer - Alberto, Matthew; Yim, Arthur; Papa, Nathan; Siva, Shankar; Ischia, Joseph; Touijer, Karim; Eastham, James A.; Bolton, Damien; Perera, Marlon (Frontiers in Oncology, 2022)
Oligometastatic prostate cancer (OMPC) has been proposed as an intermediary state between localised disease and widespread metastases, with varying definitions including 1, 3 or ≤ 5 visceral or bone metastasis. Traditional definitions of OMPC are based on staging with conventional imaging, such as computerised tomography (CT) and whole-body bone scan (WBBS). Novel imaging modalities such as Prostate Specific Membrane Antigen Positron Emission Tomography (PSMA PET) have improved diagnostic utility in detecting early metastatic prostate cancer (PC) metastases compared with conventional imaging. Specifically, meta-analytical data suggests PSMA PET is sensitive in detecting oligometastatic disease in patients with biochemical recurrence (BCR) post radical treatment of PC. Recent trials have evaluated PSMA PET guided metastases directed therapy (MDT) in oligometastatic recurrent disease, typically with salvage surgery or radiotherapy (RT). To date, these preliminary studies demonstrate promising results, potentially delaying the need for systemic therapy. We aim to report a comprehensive, multidisciplinary review of PSMA guided MDT in OMPC. In this review, we highlight the utility of PMSA PET in biochemically recurrent disease, impact of PSMA PET on the definition of oligometastatic disease and outline data pertaining to PSMA guided MDT.